A rapid and non-immersed method of viscosity measurement with small-volume samples based on longitudinal guided waves in capillary - Shaohong Qu; Songli Hu; Ting Li; Chaomin Wu; Yuexiu Chen; Linqian Zhao; Lihang Zhu; Jianjun Wu; Zhifeng Tang; Peifang Dong; Fengjiang Zhang (Sensing and Bio-Sensing Research)
Viscosity measurement is crucial in medical diagnostics, pharmaceuticals, and analytical chemistry, where samples are frequently in small volumes and measurements are supposed to be conducted in a short time with convenient approaches. In this study, we propose a viscosity measurement approach based on longitudinal guided waves with a dominant in-plane displacement. The viscosity is determined using the attenuation of longitudinal guided waves in a liquid-filled capillary. The use of guided waves accelerates the measurement while the application of a capillary reduces the sample volume. Additionally, the approach is nondestructive and repeatable since the liquid sample is injected into the capillary instead of immersing the probe into the liquid; the sample is located in a relatively closed tube, reducing the interferences of outside factors. In our propomsed method, the sample volume is only 176.6 μL and the measurement time of one sample is only 5.6 ms. The effectiveness and practicability of the proposed approach is confirmed by measuring silicon oils with viscosities from 9.01 mPa·s to 532 mPa·s and a limit of detection (LOD) of 0.97 mPa·s. The minimum error is about 5 % at 442 mPa·s and the maximum error is about 18 % at 9.01 mPa·s Besides, the approach was employed for detection of viscosity in artificial tear samples, which indicated that satisfactory applicability was achieved. This work not only demonstrates the judicious design of a rapid and non-immersed method for viscosity measurement, but also a promising scheme for point-of-care analysis of tear viscosity, thus offering great potential for at-home diagnosis and personalized healthcare of various ocular diseases.